Applications of Fianite in Electronics. (19th December 2012) - Buzynin, Alexander N.; Buzynin, Yury N.; Panov, Vitaly A.
Abstract : Fianite or yttrium stabilized zirconia (YSZ) solid solutions single crystals were known worldwide as jewelry material. The review is devoted to novel applications of the material in the field of microelectronics. A number of modern aspects of the application of fianite in micro-, opto- and SHF-electronics were analyzed in this paper. It was demonstrated that fianite is an extremely promising multipurpose material for new electronic technologies due to unique combination of physical and chemical properties. As a substrate and buffer layer for the epitaxy of Si, Ge, GeSi and A III B V compounds (GaAs, InGaAs, GaSb, InAs, GaN, AlN), fianite has a number of advantages over the other dielectric materials. The use of fianite (as well as ZrO2 and HfO2 oxides) instead of SiO2 as gate dielectrics in CMOC technology seems to be of peculiar interest. The unique properties of fianite as protecting, stabilizing and antireflecting coatings in electronics and optoelectronic devices have been outlined. A comparative study of the performance characteristics of fianite and conventional materials has been carried out.